Potret Pengelolaan Berkelanjutan Taman Wisata Alam Gunung Tunak Kabupaten Lombok Tengah - Aryan Agus Pratama; Restu Alpiansah; Ika Yuliana; Agus Hermanto (Target : Jurnal Manajemen Bisnis, 2023)
Gunung Tunak Natural Tourism Park (TWA Gunung Tunak) is a conservation area developed as a tourist area with the concept of community-based eco-tourism. Including as a buffer destination for the sustainability of the Mandalika special economic zone (KEK Mandalika) so that it must have good and sustainable management. This study aims to explore and assess the sustainability of the management of TWA Gunung Tunak since it was first opened as a tourist destination until now. This study uses a qualitative approach with content analysis. Data obtained through observation, in-depth interviews and document study. The findings of this study are divided into two categories, namely the strongest potential and participatory management. The potential of TWA Gunung Tunak has been managed with an integrated collaborative approach through the local community's Tunak Besopok forum. Management of diversity of flora and fauna is preserved with a strong socio-cultural culture of the community. Participatory management involving elements of the local community supports the sustainable management of TWA Gunung Tunak.